Moderating effect of institutional quality on the FDI-energy consumption nexus in selected African countries - Oyefabi, Ilemobola Solomon; W. N., W. Azman Saini; Muhamad Senan, Mohamad Khair Afham (Human Resources Management Academic Research Society (HRMARS), 2024)
This study examines the moderating effect of institutional quality in FDI and energy consumption relationship in Africa spanning from 1996 to 2021. The analysis focuses on four of Africa's leading FDI recipient countries: Egypt, South Africa, Mozambique, and Ghana. The result of the Dynamic ARDL simulation techniques revealed that FDI increases energy consumption in Egypt, Mozambique, and Ghana in both the short and long run. In the case of South Africa, the result reported that FD1 reduces energy consumption in both the short run and long run. The inverted EKC U-shaped relationship between FDI and energy consumption was confirmed in Egypt, Mozambique, and Ghana, however, in the case of South Africa, the inverted EKC U-shaped was invalidated. The empirical evidence further indicates that the combined effect of FDI and institutional quality mitigates energy consumption for all sampled countries. This highlights the inherent limitations of FDI alone in realizing its full benefits and emphasizes the need for a strong institutional framework to fully leverage this capital. However, without vibrant institutions that are well-functioning, the positive effects of FDI on energy efficiency may be hampered. Hence, the presence of good institutions in a host country helps boost FDI absorptive capacity which has an important role in decreasing energy demand and promoting innovative adoption by increasing the substitutability between fossil fuels and energy-efficient technologies.